Assessment of suicidal risk and its associated factors amongst medical undergraduate students in a tertiary care center: a cross-sectional observational study - Srinivasan, Sahana; Sureshkumar, Arvind Kumar; Agarwal, Prerna; Sanbak, Nusaifa A. K.; Dahiya, Shubham; P., Arulmozhi; S. Arun Murugan (International Journal Of Community Medicine And Public Health, 2024)
Background: Suicide ideation among medical students is a significant mental health concern globally. The demanding nature of medical education, combined with various personal and professional stressors, makes medical students vulnerable to mental health issues, including depression and suicidal thoughts. Methods: 250 medical undergraduate students from Government Medical College, Omandurar Government Estate were chosen. The risk of suicide was assessed through the suicide behaviors questionnaire - revised criteria (SBQ-R criteria). Scores were calculated for each response and analyzed. Results: The study revealed that 13.5% of students experienced self-destructive thoughts, with 39.4% contemplating or attempting suicide; 26.1% felt they might attempt suicide someday, and 6.1% had attempted more than five times in the past year. Despite this, only 20% shared their suicidal thoughts with trusted individuals. Academic stressors were significant, with 26.9% struggling with the heavy curriculum, 16.3% with low scores, and 5.3% affected by patient suffering. Family support was crucial but underutilized, with only 20.4% seeking family help in distress. Alcohol consumption was reported by 25.3%, relationship pressures affected 23.7%, and 4.5% by social media pressures. Conclusions: The study highlights a significant prevalence of suicidal ideation among medical students, underscoring a critical public health concern. The findings suggest that the rigorous demands of medical education, combined with high stress levels and mental health challenges, contribute to this alarming trend. Addressing these issues requires comprehensive support systems, including accessible mental health services, stress management programs, and a nurturing educational environment.